MANAGEMENT OF DIABETES WITH COVID-19: A REVIEW - KUMARI, RITU; KAUR, JAGJIT; HUSSAIN, SADIQUE (International Journal of Pharmacy and Pharmaceutical Sciences, 2020)
Objective: As of now, the world is struggling with a serious pandemic of disease 2019 Coronavirus (COVID-19), which was emerged from Wuhan in China, originated by the novel coronavirus 2019 (SARS-CoV-2). COVID-19 is a viral illness, which is occurring on a large scale in every nation of the globe. Symptoms of coronavirus mainly include fever, fatigue, cough, headache, pneumonia and in severe condition, there is respiratory distress. The deadly virus alarmed the world to be on high alert as the number of rising cases and the death toll rising as the day passes. Methods: We have searched for articles of preference and interest systematically in sources like Google Scholar, PubMed, and other outlets. Results: Management in the case of diabetes is really necessary to decrease their mortality. Certain management parameters need to be followed to take care of patients suffering from both diseases. Conclusion: In this review, we highlighted the role of different medicines like chloroquine, lopinavir, and hydroxychloroquine for the remedy of this pandemic. We also discussed the chest Computed tomography functions and Real-time polymerase chain reaction for the screening of the outbreak. The center of attention of this review majorly on the care of diabetes throughout the time of the COVID-19 epidemic.